Analysis of the Implications of the Water Convention and Protocols for Water and Health - Jusuf, Ester Indahyani; Allagan, Tiurma Mangihut Pitta; Eryando, Tris (Indonesian Journal of International Law, 2024)
Many international conventions contain positive values for humanity, which are in line with the human rights values guaranteed by our country’s constitution. The Indonesian state constitutionally guarantees the right of every Indonesian citizen to live a healthy and prosperous life, including providing water for every Indonesian citizen. However, it turns out that the Indonesian State has so far chosen not to ratify or access the Water Convention and the Water and Health Protocol, the contents of which are the good intentions of the countries participating in the convention to maintain the availability and quality of world water. This article provides a descriptive overview and comparison between the standards of the Water Convention and the Protocol on Water and Health of WHO (the Water Convention), alongside relevant Indonesian laws, namely Presidential Regulation of the Republic Indonesia Number 37 of 2023. Despite the participation of 52 states to the Water Convention 1992, Indonesia has yet to do so. The government of Indonesia has made numerous efforts that are in line with the objectives and contents of the Water Convention. However, it is undeniable that Indonesia will encounter problems and challenges if it pursues the process of accession. The problems might emerge from the perspectives of legal, public health, as well as social and economic. Considering the potential logical consequences, this article suggests Indonesia is currently adhering to the stipulation outlined in the Water Convention despite the absence of willingness to accede to it. The research employs a doctrinal approach, concurrently examining the norms and regulations inherent in the Water Convention and the newly Indonesian regulation on water management and the standards of water. Research question: Is the attitude of the Indonesian State not to ratify or access the Water Convention and the Water and Health Protocol contrary to the constitution and the principles given to Indonesian Human Rights, namely the right to life?This question was born by considering sociological rules or legal policies that one of the requirements for humans to be able to live is health. One way for human swimmers to be healthy is the availability of water in good quantity and quality throughout their lives. This research uses a public policy analysis approach, especially the theory of George C. Edwards III, with observations of state financial administration in the process of implementing human rights. The novelty of this article predicts the impact of the ratification of the Water Convention and the Water and Health Protocol for the Indonesian people; The contestation includes human rights in the field of clean water by including human rights in other fields as well as Indonesia’s political economic interests.